2012
DOI: 10.1097/olq.0b013e31825ef325
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Condom Use Problems During Vaginal Sex With Main and Non-Main Partners

Abstract: Background Incorrect condom use is a common problem that can undermine their prevention impact. We assessed the prevalence of two condom use problems, breakage/slippage and partial use, compared problems by partnership type, and examined associations with respondent, partner, and partnership characteristics. Methods Data were collected at 3-month intervals over a 12-month period (1999–2000) among urban STD clinic users. Condom use problems were compared between partnership types using z-tests for equality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…The significance of this arises from findings of a 2011 systematic review which concluded that alcohol consumption was an independent risk factor for intent to engage in unprotected sex [32]. D'Anna et al [33] found that sex whilst under the influence of drugs or alcohol was the single most significant predictor for condom use problems amongst those attending an STI clinic. Furthermore, our sample reported a high level of recent alcohol consumption, with 34% of participants consuming 10 or more standard drinks in the past 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this arises from findings of a 2011 systematic review which concluded that alcohol consumption was an independent risk factor for intent to engage in unprotected sex [32]. D'Anna et al [33] found that sex whilst under the influence of drugs or alcohol was the single most significant predictor for condom use problems amongst those attending an STI clinic. Furthermore, our sample reported a high level of recent alcohol consumption, with 34% of participants consuming 10 or more standard drinks in the past 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…De Visser et al [35] in 2003 conducted telephone interviews of 10,173 16–59-year-old Australian men, finding that 23.8% had experienced at least one condom breakage in the past year and 18.1% had experienced at least one condom slippage over the same time. The higher incidence of failures found in festival attendees may in part be explained by younger age of participants and subsequent likelihood to engage in high risk sexual behaviours [33, 35]. Problems with condom use has not yet been investigated in this population, and to our knowledge this is the first study to demonstrate that young Australian festival attendees may be experiencing significantly higher rates of problems when using condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Condoms are relatively free from side effects. The main drawback to condoms is their marginal contraceptive efficacy, which results mostly from improper or inconsistent usage, or breakage, which occurs in up to 4% of cases (19). Pregnancy rates for couples using condoms as their sole means of contraception approach 15–20% per year (20), although failure rates are likely higher in young couples with high spontaneous fertility (21).…”
Section: Currently Available Male Contraceptive Methodsmentioning
confidence: 99%
“…Pregnancy rates for couples using condoms for contraception are 10–15% per year, and rates of pregnancy are higher in younger couples with greater fecundity. Condom failure can result from improper usage, or breakage, which occurs up to 4% of the time . In addition, some men dislike condoms because they find them difficult to use or feel that they diminish sexual pleasure .…”
Section: Currently Available Male Contraceptive Methodsmentioning
confidence: 99%
“…Condom failure can result from improper usage, or breakage, which occurs up to 4% of the time. 27 In addition, some men dislike condoms because they find them difficult to use or feel that they diminish sexual pleasure. 28 Last, some people have allergic reactions to the latex, which is allergenic and can lead to penile or vaginal irritation and even anaphylaxis, although this is rare.…”
Section: Condomsmentioning
confidence: 99%